S-BPM Illustrated A Storybook about Business Process Modeling and Execution - Fleischmann, Albert; Raß, Stefan; Singer, Robert (Springer Berlin Heidelberg : Imprint: Springer, 2013)
S-BPM stands for “subject-oriented business process management” and focuses on subjects that represent the entities (people, programs etc.) that are actively engaged in processes. S-BPM has become one of the most widely discussed approaches for process professionals. Its potential particularly lies in the integration of advanced information technology with organizational and managerial methods to foster and leverage business innovation, operational excellence and intra- and inter-organizational collaboration. Thus S-BPM can also be understood as a stakeholder-oriented and social business process management methodology. In this book, the authors show how S-BPM and its tools can be used in order to solve communication and synchronization problems involving humans and/or machines in an organization. All the activities needed in order to implement a business process are shown step by step; it starts by analyzing the problem, continues with modeling and validating the corresponding process, and finishes off by embedding the process into the organization. The final result is a workflow that executes the process without the need for any programming. To this end, in the first step a very simple process is implemented, which is subsequently extended and improved in “adaption projects,” because additional problems have to be solved. This approach reflects the organizational reality, in which processes must always be changed and adapted to new requirements. This is a hands-on book, written by professionals for professionals, with a clear and concise style, a wealth of illustrations (as the title suggests), and focusing on an ongoing example with a real industrial background. Readers who want to execute all the steps by themselves can simply download the S-BPM tool suite from the www.i2pm.net website.